Reintroducing Single Group Flashes to Improve Geostationary Lightning Mapper Detection Efficiency - Mach, Douglas M.; Bateman, Monte G. (Journal of geophysical research. Atmospheres, 2025)
The Geostationary Lightning Mapper (GLM) is a near‐infrared, single‐channel optical transient detector on the NOAA Geostationary Operational Environmental Satellites‐R Series (GOES‐R). Its purpose is to continuously detect both cloud and ground flashes during day and night, with high spatial resolution and detection efficiency (DE). One of the filters in the lightning cluster filter algorithm removes all flashes with group counts of less than two. This single group flash (SGF) filter was implemented to remove spurious nonlightning detections by the GLM that increased the instrument the false alarm rate (FAR) and decreased the DE. In this analysis, we examine some of the SGF characteristics and the relationships to other flashes detected by GLM to determine if any of those parameters can be used to determine which SGFs are likely from lightning. The analysis focuses on the impacts of including SGFs on the DE and FAR values by comparing the results to those calculated from an independent data source consisting of flashes from the global lightning detection network, and Earth Network's Global Lightning Network stroke data. We find that the best indicator of the lightning/nonlightning status of SGFs is the SGF's proximity (in time and space) to flashes with multiple groups. We find that a temporal separation of less than 1.6 s and a spatial separation of less than 64 km from a multigroup flash provides the best combination of the maximum DE (0.12) and the minimum FAR (0.02). Plain Language Summary The Geostationary Lightning Mapper (GLM) is an instrument on the NOAA Geostationary Operational Environmental Satellites‐R (GOES‐R) Series. There is one on GOES‐East (GLM‐16) and one on GOES‐West (GLM‐17). The GLM data are processed into a series of events, groups, and flashes. Events are single pixels that exceed the threshold at a single time. Groups are collections of adjacent events at the same time. Flashes are collections of groups within 330 ms and 16.5 km of each other. One of the current filters in the GLM algorithm removes all flashes that have only a single group. We found that some of those removed single group flashes are from lightning. We examined several methods to determine which of those single group flashes were lightning. The best method, based on how many more lightning flashes we can add without adding too many false flashes was to look for single group flashes that were near flashes that had more than one group. Key Points Flashes with only a single group are currently removed from the Geostationary Lightning Mapper data set Some of these single group flashes are lightning Single group flashes most likely to be lightning are those nearest flashes with multiple groups